Attitudes - "Jahoda , Marie (ed.)" ("Middlesex, Eng.", 1966)
The Study of attitudes has always been a central topic in social psychology, from research data on particular social groups to recent extensive analysis, in experiment field work and theory, on attitude change.
Keywords: Attitude (Psychology)